Synthesis of amorphous hydroxyl-rich Co3O4 for flexible high-rate supercapacitor - Tao, Yingjie; Wu, Yatao; Chen, Hao; Chen, Weijie; Wang, Jiajie; Tong, Yifei; Pei, Gu; Shen, Zhehong; Guan, Cao (Chemical engineering journal (Lausanne, Switzerland : 1996), 2020)
[Display omitted] •Novel Co3O4 flexible electrode is fabricated via electrochemical oxidation of Co-MOF.•This Co3O4 electrode owns the amorphous hydroxyl-rich hierarchical structure.•It expresses higher Cs than a highly crystalline hydroxyl-deficient Co3O4 electrode.•It also exhibits better rate performance than many cobalt oxide-based electrodes.•ASC based on this electrode shows excellent rate capability and cycling performance. Metal oxides-based materials are promising electrodes for energy storage devices, however, the low rate performance and the high energy consumption in the preparation limit their practical applications. Herein, a novel amorphous hydroxyl-rich Co3O4 hierarchical structure flexible electrode is facilely fabricated via electrochemical oxidation of a cobalt-based metal-organic framework. The as-prepared Co3O4 hierarchical structure is composed of large microrods and small nanoparticles and possesses abundant mesopores, amorphous, and hydroxyl-rich nature. These characteristics favor rapid electron transfer, complete exposure of the active interface, and sufficient penetration of electrolyte ions within the active material. Benefitting from these advantages, the optimal Co3O4 electrode (Co3O4-5) expresses a high reversible specific capacitance (Cs) of 226.1 C·g−1 (or 253.2 mC·cm−2), which is 2 (or 3.7) times higher than those of highly crystalline hydroxyl-deficient Co3O4 electrode. The Co3O4-5 electrode also shows excellent rate performance (97% Cs retention after a 6.7-times current increasing), which surpasses the levels of many cobalt oxide-based electrodes. In addition, an asymmetric supercapacitor (ASC) constructed from this Co3O4-5 electrode achieves a large energy density of 26.6 Wh·kg−1 (or 0.146 mWh·cm−2), outstanding rate capability (1% Cs loss at the 10-fold higher current density), and stable cycle performance (10.1% Cs loss after 20,000 charge-discharge cycles).